2004
DOI: 10.1161/01.cir.0000147781.02738.13
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Mapping of Chronic Atrial Fibrillation in Patients

Abstract: Background-The mechanisms of chronic atrial fibrillation (AF) are not well understood. We performed epicardial mapping of chronic AF in patients undergoing open heart surgery to test the hypothesis that chronic AF is due to a left atrial "driver" with a regular, short cycle length, resulting in fibrillatory conduction to the rest of the atria. Methods and Results-Nine patients with chronic AF (1 month to Ͼ15 years' duration) were studied at open heart surgery, 8 before and 1 during cardiopulmonary bypass. Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
192
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(205 citation statements)
references
References 16 publications
(20 reference statements)
12
192
0
1
Order By: Relevance
“…Since optical dye fluorescence techniques employed in animal studies cannot be used in humans due to concerns over toxicity, contact electrode arrays are the most common mapping modality 13,14 although non-invasive and non-contact techniques using the inverse solution have been developed. 40,41 Contact arrays have been used to determine the spatio-temporal organization during human AF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since optical dye fluorescence techniques employed in animal studies cannot be used in humans due to concerns over toxicity, contact electrode arrays are the most common mapping modality 13,14 although non-invasive and non-contact techniques using the inverse solution have been developed. 40,41 Contact arrays have been used to determine the spatio-temporal organization during human AF.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Mapping wide fields of view in animal studies is achieved in isolated heart preparations, while human mapping has been achieved either using contact electrode plaques on regions of the heart accessible during open heart surgery or using relatively few electrodes at percutaneous electrophysiology study. 13,14 Despite these studies, however, the mechanisms of human AF remain highly controversial, 7,15 and AF therapy has not advanced significantly in several years. 11,16 Ideally, human AF would be mapped in situ during clinical electrophysiologic study to avoid open heart surgery while enabling direct therapy (ablation) based upon patientspecific mapping results.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, 9 patients with chronic AF the atrial electrogram showed an area of regular, rapid rhythm, consistent with the possibility that a driver causing fibrillatory conduction is one mechanism of AF in these patients. 36 Finally, in the study of Atienza et al, 33 ADO infusion in persistent AF patients increased local DFs only in the high RA, without significant changes at other atrial sites. Those data suggested that persistent AF also is maintained by high-frequency reentrant sources.…”
Section: Are There Rotors In the Human Atrium?mentioning
confidence: 93%
“…Mechanizmem tej ogniskowej aktywności może być zarówno aktywność wyzwalana, jak i ogniskowo występujące zjawisko re-entry [109,110]. Hierarchiczną organizację AF z szybką aktywacją obszarów napędzających arytmię udokumentowano u pacjentów z napadowym AF [111,112], ale jest mniej oczywista u nieselekcjonowanych pacjentów z przetrwałym AF [113].…”
Section: Ogniskowa Inicjacja I Podtrzymywanie Migotania Przedsionkówunclassified